Process of Deinstitutionalization of Aging Individuals With Severe and Disabling Mental Disorders: A Review - Salime, Samira; Clesse, Christophe; Jeffredo, Alexis; Batt, Martine (Frontiers in Psychiatry, 2022)
Background: For more than 60 years, psychiatric services has gradually gone from an asylum model to a community model. This change has led to the emergence of a deinstitutionalization movement. This movement seems to have left behind long-term hospitalised aging individuals with severe and disabling mental disorders. The objective of this article is to conduct a review on the challenges and issues associated with the process of deinstitutionalization among hospitalised aging individuals with severe and disabling mental disorders. Methods: Using PRISMA statement, the research methodology was carried out in English and French in 16 databases with a combination of 3 lists of keywords. The selection process was then followed by a thematic analysis which aimed at categorizing by theme and classifying the writings selected. Results: A total of 83 articles published between 1978 and 2019 were selected and organized into six categories: a) a forgotten population in research and health policies, b) an economic presentation of the deinstitutionalization process, c) an improvement in quality of life and global functioning for deinstitutionalized patients d) from stigmatization to the rejection of elderly psychiatric inpatients from deinstutionalization process, e) a difficult community-based care offer and a difficult epistemological identification, f) from the lack of community services to the phenomenon of transinstitutionalization. The current state of scientific research, institutional policies and clinical practices associated with the deinstitutionalization process of SVPTSIH are then commented. Conclusions: Recommendations are proposed to researchers and professionals concerned with the support of long-term hospitalised aging individuals with severe and disabling mental disorders.